2, 4, 6-Tribromophenol Exposure Decreases P-Glycoprotein Transport at the Blood-Brain Barrier. (2nd August 2019) - Trexler, Andrew W; Knudsen, Gabriel A; Nicklisch, Sascha C T; Birnbaum, Linda S; Cannon, Ronald E
Abstract: 2, 4, 6-Tribromophenol (TBP, CAS No. 118-79-6) is a brominated chemical used in the production of flame-retardant epoxy resins and as a wood preservative. In marine environments, TBP is incorporated into shellfish and consumed by predatory fish. Food processing and water treatment facilities produce TBP as a byproduct. 2, 4, 6-Tribromophenol has been detected in human blood and breast milk. Biologically, TBP interferes with estrogen and thyroid hormone signaling, which regulate important transporters of the blood-brain barrier (BBB). The BBB is a selectively permeable barrier characterized by brain microvessels which are composed of endothelial cells mortared by tight-junction proteins. ATP-binding cassette (ABC) efflux transporters on the luminal membrane facilitate the removal of unwanted endobiotics and xenobiotics from the brain. In this study, we examined the in vivo and ex vivo effects of TBP on two important transporters of the BBB: P-glycoprotein (P-gp, ABCB1) and Multidrug Resistance-associated Protein 2 (MRP2, ABCC2), using male and female rats and mice. 2, 4, 6-Tribromophenol exposure ex vivo resulted in a time- (1–3 h) and dose- (1–100 nM) dependent decrease in P-gp transport activity. MRP2 transport activity was unchanged under identical conditions. Immunofluorescence and western blotting measured decreases in P-gp expression after TBP treatment. ATPase assays indicate that TBP is not a substrate and does not directly interact with P-gp. In vivo dosing with TBP (0.4 µmol/kg) produced decreases in P-gp transport. Co-treatment with selective protein kinase C (PKC) inhibitors prevented the TBP-mediated decreases in P-gp transport activity.